A Research Agenda for Climate Change Communication and Public Opinion: The Role of Scientific Consensus Messaging and Beyond. Issue 1 (2nd January 2023) - Bayes, Robin; Bolsen, Toby; Druckman, James N.
ABSTRACT: That climate change has been accelerated by human activity is supported by a near-universal consensus of climate scientists. In this paper, we review many of the studies that have been done on the impact of communicating the scientific consensus to the general public. We discuss ongoing debates about these studies, but more importantly, we highlight complementary areas that we believe should define future research. We emphasize how a focus on processing motivations, context, and message variations may help resolve some of the debates about when scientific consensus messaging works. We then discuss ways to expand this research agenda by examining support for a broader range of outcomes across a wider range of populations, particularly those most vulnerable to the immediate impacts of climate change. Our goal is to provide a blueprint for expanding the work on climate change communication for scientific consensus messaging and beyond.